Elaboración de un recorrido virtual interactivo 360º grados del atractivo turístico Puerto Bajaña del cantón Buena Fe provincia de Los Ríos 2020. - Barre Briones, Thalia Lilibeth (2020)
The objective of the following research was to develop a 360º degree interactive virtual tour of the tourist attraction Puerto Bajaña in the canton of Buena Fe, province of Los Ríos, year 2020. The descriptive method was used to describe the characteristics of the Puerto Bajaña attraction and to inform users about its tourist offer. Surveys were applied to 379 inhabitants of the Buena Fe canton, which allowed to know the degree of interest in the implementation of a 360° virtual tour in the attraction. The main results showed that 71.65% know about the attraction and 76.96% are interested in taking the virtual tour; therefore, the implementation of this project would generate income for both the attraction and the canton of Buena Fe. The elaboration of the tour in the web page Paneek - free 360° virtual tour software, allows visualizing a pleasant tour of the attraction, knowing the tourist facilities offered in Puerto Bajaña. In conclusion, due to the current situation in the country and the world, tourism has stopped in many areas and its reactivation has been generated slowly but ensuring the welfare of tourists. For this reason the execution of this research work can awaken interest in visiting the place in the future to those who visualize the tour. Key words: Interactivity, virtual tour, tourist attraction.